1983
DOI: 10.1104/pp.73.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of l-Ascorbate by Intact Spinach Chloroplasts

Abstract: ABSTRACIUptake of l1-4Cjascorbate by intact ascorbate-free spinach (Spinacia okracca L. cv Vital) chloroplasts has been investigated using the technique of silicone oil filtering. Rates greater than 100 micromoles per milligrm chlorophyll per hour (external concentration, 10 millimolar) of ascorbate transport were observed. Ascorbate uptake into the sorbitolimpermeable space (stroma) followed the Michaelis-Menten-type characteristic for substrate saturation. A K. of 18 to 40 millimolar was determined. Transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…However, the presence of ascorbate / DHA transporters has been demonstrated in chloroplasts (Beck et al, 1983) and in protoplasts and vacuole membranes (Rautenkranz et al, 1994). In this case, if in the latency assays ascorbate is transported rapidly across the membrane, the APX would have access to its substrate regardless of its location.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of ascorbate / DHA transporters has been demonstrated in chloroplasts (Beck et al, 1983) and in protoplasts and vacuole membranes (Rautenkranz et al, 1994). In this case, if in the latency assays ascorbate is transported rapidly across the membrane, the APX would have access to its substrate regardless of its location.…”
Section: Discussionmentioning
confidence: 99%
“…This would fulfill both the requirement of protecting mitochondria against H 2 O 2 and of being transported across the mitochondrial membrane in the oxidized form. Whether the oxidized form of AsA is the only one transported across membranes is still an open question, since evidence for the transport of AsA in the reduced form into intact chloroplasts has been provided (Beck et al, 1983). In this work we have studied AFR reductase, which catalyzes the regeneration of AsA from its first oxidation product, AFR.…”
Section: Purification Of Mitochondrial Afr Reductasementioning
confidence: 99%
“…Transport of ASC in plant cells was first demonstrated in purified intact chloroplasts of spinach (Anderson et al, 1983;Beck et al, 1983). Beck et al (1983) suggested that this is a carrier-mediated process that translocates ASC across the chloroplast envelope by a facilitated diffusion mechanism.…”
mentioning
confidence: 99%
“…Beck et al (1983) suggested that this is a carrier-mediated process that translocates ASC across the chloroplast envelope by a facilitated diffusion mechanism. The chloroplast ASC carrier shows a rather low affinity (approximately 20 mM) and is inhibited by the addition of the sulfhydryl reagent p-chloromercuribenzene sulfonic acid and by the oxidized DHA but not by Glc (Beck et al, 1983;Foyer and Lelandais, 1996). The latter effect led to the suggestion that different carriers for Glc and ASC exist in the chloroplast membrane (Foyer and Lelandais, 1996).…”
mentioning
confidence: 99%